Novel metallic states at low temperatures - Rowley, S.E.; Smith, R.P.; Marcano, N.; Dean, M.P.M.; Kusmartseva, A.; Spalek, L.J.; O'Farrell, E.C.T.; Tompsett, D.A.; Sutherland, M.L.; Alireza, P.L.; Ko, C.; Liu, C.; et al. (Физика низких температур, 2011)
We present an overview of unconventional metallic states arising close to magnetic quantum critical points with a focus on d-electron systems. The applicability and potential breakdowns of traditional self-consistent field theories of such materials are discussed as well as related phenomena in other systems.